2011
DOI: 10.3319/tao.2011.07.04.01(tm)
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Statistical Typhoon Rainfall Forecasting with ANN-Based Southwest Monsoon Enhancement

Abstract: Typhoon Morakot 2009, with significant southwest monsoon flow, produced a record-breaking rainfall of 2361 mm in 48 hours. This study hopes to improve a statistical typhoon rainfall forecasting method used over the mountain region of Taiwan via an artificial neural network based southwest monsoon enhancement (ANNSME) model. Rainfall data collected at two mountain weather stations, ALiShan and YuShan, are analyzed to establish the relation to the southwest monsoon moisture flux which is calculated at a designat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…Warm ocean eddies in the vicinity of Morakot's path also are closely involved in the enhancement of local convection embedded in Morakot . On the other hand, the synoptic environments were also favorable for convective instability to occur; for example, our model results indicate that very large CAPE (up to 3000 J kg -1 ) existed over the oceanic region covering the Morakot spiral circulation and the southwesterly monsoon belt that both transported abundant water vapor to south Taiwan which is in agreement with the observational study (Pan et al 2011). The atmospheric flow in fact exhibited convective instability to a depth of about 10 km just west of south Taiwan.…”
Section: Discussionsupporting
confidence: 77%
“…Warm ocean eddies in the vicinity of Morakot's path also are closely involved in the enhancement of local convection embedded in Morakot . On the other hand, the synoptic environments were also favorable for convective instability to occur; for example, our model results indicate that very large CAPE (up to 3000 J kg -1 ) existed over the oceanic region covering the Morakot spiral circulation and the southwesterly monsoon belt that both transported abundant water vapor to south Taiwan which is in agreement with the observational study (Pan et al 2011). The atmospheric flow in fact exhibited convective instability to a depth of about 10 km just west of south Taiwan.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have proposed several methods to forecast long-term or short-term precipitation patterns or classify the characteristics of typhoons, including machine learning methods that use artificial neural networks (ANN) or support vector machines (SVM) (French et al 1992;Kuligowski and Barros 1998;Lin and Chen 2005;Lin and Wu 2009;Pan et al 2011). In addition, ensemble meteorological models include perturbations in the initial conditions, data-analysis methods, and physical parameterizations to forecast typhoon rainfall (Hsiao et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Pan et al (2007) demonstrated that DLRNN (one type of SSNNs) only needs the current rainfall as the input to get a satisfactory hydrograph while an FNN, which has the same input and number of weights as the DLRNN, performs rainfall-runoff processes poorly. Pan et al (2011) used an ANN-based southwest monsoon rainfall enhancement (AME) to improve TRCM rainfall forecasting for two mountain stations Alishan and Yushan with cumulative rainfall over 400 mm. Their result suggested that AME improves TRCM rainfall predictions significantly in both mountain stations.…”
Section: Introductionmentioning
confidence: 99%